Konstruksi Feminisme terhadap Budaya Bali dalam Novel Kalamata Karya Ni Made Purnama Sari - Vivian Nur Safitri; Purwati Anggraini (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2020)
In general, the culture of society places women second, while the top hierarchy is occupied by men. This revealed that women were still marginalized. The role of women is not only the main character that must be under the men but also has the same rights struggle without involving gender. Many people still hold a strict patriarchal culture so as to produce gender biased decisions and attitudes that affect women's struggle to achieve equal positions. The existence of these problems can be built by the woman with the culture represented in the Kalamata novel with the role of the woman playing the role of the mastermind. This study aims to describe the overall values of feminism in the involvement of women in cultural aspects. The method used is a descriptive qualitative approach to feminism. Source of data is a collection of stories in a novel entitled Kalamata written by Ni Made Purnama Sari. Data analysis included descriptions performed after data collection, data interpretation, and data inference. The results of the study are discussed in the attitudes of women leaders in culture, the influence of women leaders on cultural development, the role of women leaders in education and the problem of women leaders in cultural preservation.